Pengaruh Pendidikan Kesehatan Menggunakan Media Video Animasi Terhadap Kesiapan dan Pengetahuan dalam Menghadapi Menarche: The Influence of Health Education Using Animation Video Media on Readiness and Knowledge in Facing Menarche - Sari, Diah Wulan; Hardiyanti, Diana; Pertiwi, Melinda Restu (Lentora Nursing Journal, 2023)
Background: Menarche (first menstruation) is the culmination of a series of primary and secondary changes that occur in young women. Menarche will be a traumatic event for some young women who are not prepared for it. Lack of information and knowledge about reproductive health, especially menstruation affects adolescents' perceptions of menarche. Purpose: : to determine the effect of Health Education using animated video media on readiness in dealing with menarche at SDN Jawa 5 Martapura. Methods: this research is quantitative with a pre-experimental research design type of one group pretest-posttest design. Results: this study shows that there is an effect of health education using animated video media on readiness in facing menarche at SDN Jawa 5 Martapura with a p-value of 0.001 < (0.05). Conclusion: it can be seen that there is an effect of health education using animated video media on readiness in facing menarche. is expected to increase knowledge and insight for respondents regarding readiness in facing menarche. One way to increase preparedness in facing menarche is to increase knowledge through the provision of health education about menstruation